(untitled) (Research, Society and Development, 2022)
One characteristic that can be observed in family farming is the diversity of activities that are carried out concurrently on the property, providing and guaranteeing products for personal consumption or sale over the course of the year. Fish farming, an activity destined for fish production, is often one of these activities developed by family farmers and contributes to the access to quality protein for rural families and to increase income. Furthermore, the techniques used for fish production in family farming can foment a sustainable form of production. However, the lack of incentives regarding extension projects, marketing barriers, the lack of integration of traditional communities in decision making, and the absence of adequate technical information for the reality of rural properties make this activity limited and even ineffective in some regions. The encouragement of this activity could provide family farmers with improved economic conditions and food security and, consequently, the reduction of poverty in rural areas. The present study originated from a bibliographic review that addresses the activity of fish production and its impacts on the development of rural family activities, food security, and public and social policies for the maintenance, regularity, and quality of the final product.